Honoring Roger Weissberg’s legacy by centering relationships, collaboration, and the wellbeing of all children through SEL - Maurice J. Elias; Danielle R. Hatchimonji (Social and Emotional Learning: Research, Practice, and Policy)
We describe how the field of social and emotional learning (SEL) can best honor Roger Weissberg’s legacy from the perspective of an early collaborator, Maurice J. Elias, and an early career scholar who felt his influence indirectly, Danielle R. Hatchimonji. Three themes permeated Roger’s early and most influential work and continue to shape his influence today: primacy of relationships, importance of collaboration, and shared commitment to the wellbeing of children. To uphold Roger’s influence and honor his legacy, the field of SEL must make these three themes central to research, practice, and policy of social and emotional learning.